Escaping Host Factor PI4KB Inhibition: Enterovirus Genomic RNA Replication in the Absence of Replication Organelles - Melia, Charlotte E. (Cell Rep, 2017)
Enteroviruses reorganize cellular endomembranes into replication organelles (ROs) for genome replication. Although enterovirus replication depends on phosphatidylinositol 4-kinase type IIIβ (PI4KB), its role, and that of its product, phosphatidylinositol 4-phosphate (PI4P), is only partially understood. Exploiting a mutant coxsackievirus resistant to PI4KB inhibition, we show that PI4KB activity has distinct functions both in proteolytic processing of the viral polyprotein and in RO biogenesis. The escape mutation rectifies a proteolytic processing defect imposed by PI4KB inhibition, pointing to a possible escape mechanism. Remarkably, under PI4KB inhibition, the mutant virus could replicate its genome in the absence of ROs, using instead the Golgi apparatus. This impaired RO biogenesis provided an opportunity to investigate the proposed role of ROs in shielding enteroviral RNA from cellular sensors. Neither accelerated sensing of viral RNA nor enhanced innate immune responses was observed. Together, our findings challenge the notion that ROs are indispensable for enterovirus genome replication and immune evasion.